Hvilke faktorer påvirker bysykkelbruken? - Bakke, Eskild Langnes; Tørset, Trude (Proceedings from the Annual Transport Conference at Aalborg University, 2018)
The shared bicycle trips from Oslo in the 2017-season are analysed, showing which trips are taken the most, what daily and seasonally variations that exists, and how rain and temperature influences the usage of shared bicycles. The travel data are categorized by the speed, length and height difference of the trips. Linear regression analyses were conducted to understand how weather impacts different types of trips differently during different times of day. There are daily and seasonally variances in how the shared bicycles are being used. The weather impacts the number of trips, as well as the type of trips, being taken. Rain has a negative effect on the bicycle usage. Rain negatively impacts the share of long trips and trips taken at a slow pace the most, while trips taken at a fast pace and trips in the morning rush are affected the least. Higher temperatures positively affect the shared bicycle usage, with the largest effect observed in the evenings. Warm weather positively impacts the number of trips taken at a slow pace more than it impacts the number of trips taken at a fast pace. This information is useful in understanding how the weather can affect the attractiveness of the soft modes and is useful in bicycle planning.